2019
DOI: 10.1111/inm.12580
|View full text |Cite
|
Sign up to set email alerts
|

Why go to the emergency department? Perspectives from persons with borderline personality disorder

Abstract: Through this qualitative study, we explored frequent emergency department use by persons with borderline personality disorder from their perspective. Interpretive description guided the study design, and data were collected through interviews with six individuals diagnosed with borderline personality disorder who had at least 12 emergency department visits for reasons related to their mental illness within a 1‐year timeframe. Using thematic data analysis, we articulate the participants’ experiences through two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(93 citation statements)
references
References 37 publications
1
92
0
Order By: Relevance
“…Consumer peer workers and carer peer workers may also alter the practices of mental health professionals to be more recovery oriented. Providing peer support in services where stigmatized responses are heightened, including non-specialist BPD settings such as the emergency department [12], may be beneficial for consumer and carers, and could help alter the practices of professionals. However, the current study also found that consumer peer workers with BPD can experience stigma from other consumer peer workers and mental health professionals, which is consistent with previous research [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer peer workers and carer peer workers may also alter the practices of mental health professionals to be more recovery oriented. Providing peer support in services where stigmatized responses are heightened, including non-specialist BPD settings such as the emergency department [12], may be beneficial for consumer and carers, and could help alter the practices of professionals. However, the current study also found that consumer peer workers with BPD can experience stigma from other consumer peer workers and mental health professionals, which is consistent with previous research [52].…”
Section: Discussionmentioning
confidence: 99%
“…Peer support may be beneficial for consumers with BPD and their carers to help enhance recovery. Peer support has been recommended for consumers with BPD to improve relationships and sense of self [ 10 ], and to improve personality disorder services [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers with personality disorder often do not receive an explanation of their diagnosis [23], or experience stigmatizing language and insufficient evidence-based information about their diagnosis [6]. Consumers have also described negative responses from health professionals in the emergency department [24]. Other negative experiences include poor communication from professionals, and inappropriate treatment, such as not having concerns taken seriously [6].…”
Section: Introductionmentioning
confidence: 99%
“…The main finding is that the PES professionals report a complex picture of the patients' needs based on their personal and social life circumstances and on the healthcare and support context. The needs identified by the professionals correspond relatively well with those expressed by persons who frequently visit PES or emergency departments themselves Schmidt et al, 2018b;Vandyk et al, 2018Vandyk et al, , 2019Wise-Harris et al, 2017), stressing the complexity of the patients' needs and the subjective component of the patients' suffering, lack of health and well-being, and the need for human contact and social interaction. In particular, the patients' feelings of loneliness, their internal and external struggle, and their negative self-image leading to feelings of worthlessness and hopelessness were common topics discussed in studies about persons with (severe) mental illness visiting other mental health or healthcare services (Ådnøy Eriksen, Sundfør, Karlsson, Råholm, & Arman, 2012;Fleury, Grenier, Bamvita, & Tremblay, 2013;Lindgren, Sundbaum, Eriksson, & Graneheim, 2014).…”
Section: Discussionmentioning
confidence: 64%
“…In a recent Swedish mixedmethods study including persons who frequently visit PES, the participants self-reported having needs to reduce acute suffering, feel secure, and have caring encounters with PES staff, as well as needs to reduce psychological distress and psychotic symptoms and to have daytime activities (Schmidt et al, 2018b). Reviews of studies focusing on persons who frequently visit PES or emergency departments, and on their needs in particular, indicated that explanatory research has dominated the field so far (Schmidt, 2018;Vandyk, Harrison, VanDenKerkhof, Graham, & Ross-White, 2013), while exploratory research has been scarce (Vandyk, Bentz, Bissonette, & Cater, 2019;Vandyk, Young, MacPhee, & Gillis, 2018;Wise-Harris et al, 2017). In-depth qualitative studies of an explorative nature may be required to more fully understand this complex group's needs and the reasons and life circumstances underlying those needs.…”
Section: Introductionmentioning
confidence: 99%